A RETROSPECTIVE COMPARATIVE STUDY OF THE EFFECTS AND SIDE EFFECTS OF LEVETIRACETAM AGAINST SODIUM VALPROATE IN PATIENTS DIAGNOSED WITH GENERALIZED EPILEPSY - Fattahzadeh, Ghasem; Amani, Firouz; Mohammadi, Nayyereh (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Nearly one in every 28 people will receive a diagnosis of epilepsy at some point in their lives, but nearly half of those individuals do not receive treatment using the medications available today. It's still difficult to choose the right antiepileptic medication because it needs to be safe, effective, and bearable. For children older than one year, levetiracetam, a recently approved experimental antiepileptic, can be used as an adjuvant treatment for seizures. Objective: The purpose of this study was to assess levetiracetam's safety and effectiveness as an adjuvant treatment for epilepsy in Iranian children and adults. Method: Methods: Two groups of 100 patients each receiving treatment with sodium valproate and levetiracetam were included in this cross-sectional and analytical study, which involved 200 patients with generalized epilepsy who were referred to the neurology clinics of Alavi Hospital in Ardabil between 2014 and 2019. By looking through the patient files, the necessary data was gathered, such as demographics, drug side effects, degree of satisfaction with the course of therapy, and the drug's effectiveness in controlling seizures. Based on the study's goals, pertinent data was assessed by entering it into the SPSS version 17 program. Results: Findings: There was no significant difference in the average age or gender distribution between the two groups receiving sodium valproate and levetiracetam treatment (P=0.203 and P=0.384, respectively). Headache and nausea were the most frequent adverse effects of sodium valproate and levetiracetam, respectively. While 71% of patients treated with sodium valproate had good seizure control (P<0.001), 23% and 55% of patients treated with Lobel medication had moderate and good seizure control, respectively. Additionally, 68% of the Sodium Valproate group reported good satisfaction with the treatment, compared to 50% and 24% of the Lobel receiving group (P<0.001). While 20% of patients treated with sodium valproate experienced more than three pharmacological issues, the majority of patients (82%) treated with Lobel experienced no drug difficulties at all. Conclusion: Despite its poor performance in this area when compared to sodium valproate, the Lobel medication generally has positive effects on seizure control and patient satisfaction. On the other hand, patients treated with Lobel have experienced significantly fewer drug side effects than those treated with sodium valproate.